AB0788B RECOMENDATIONS FOR DISEASE ACTIVITY ASSESSMENT AND DEFINITION OF CLINICAL REMISSION IN PSORIATIC ARTHTITIS: A DELPHI-BASED EXPERT CONSENSUS. (June 2019) - Almodovar, Raquel; Cañete, Juan D.; Miguel, Eugenio de; Pinto Tasende, Jose antonio; Silva, Rubén Queiró
Abstract : Background: Patients with psoriasis arthritis (PsA) have heterogeneous clinical presentations, with diverse articular and dermatological features and varied disease courses and outcomes, so the assessment of disease activity implies important difficulties. Although the goal of treatment of PsA is to achieve remission, there is no a universally accepted definition. Objectives: The purpose of this study was to assess agreement by experts on recommended disease activity assessment in PsA patients and to develop a consensus definition of clinical remission. Methods: A modified Delphi approach was used as a consensus method. A scientific committee of experts provided 86 statements that were submitted in 2 rounds to a panel of 130 Spanish experts in PsA (in September and October 2018, respectively), addressing issues regarding the current assessment of remission, variables that should be included in the minimal assessment of PsA patients and the definition of remission, and the use of disease activity scores. Results: The expert panel reached agreement for 53 proposed statements (61.6%). There was consensus that the definition of remission in PsA should include: the absence of signs and symptoms, physical well-being, the absence of impact of the disease, the absence of inflammation and progression in imaging tests (radiography and magnetic resonance) and the absence of inflammation measured by biomarkers (ESR, CRP). It is recommended to use some index designed specifically for the assessment of disease activity and the variables that should include the minimal assessment of PsA patients are: painful/swollen joints, enthesitis, dactylitis, axial involvement, skin and nail involvement, physical function, quality of life, structural damage assessed by imaging techniques, CRP, both patient and physician global assessment, both patient and physician skin assessment and extra-articular manifestations. The use of a treat-to-target (T2T) strategy should be considered in PsA patients, especially in those with a high risk of progression of structural damage. Although the ideal therapeutic goal is remission, there is consensus that low disease activity (LDA) is an acceptable goal. The most recommended tool to assess the disease activity in the clinic is DAPSA, with cut-off values of ≤ 4 for remission and > 4 to 14 for LDA. In patients who have reached the minimum activity of the disease, there was agreement in which the most suitable index was the MDA (Minimal Disease activity), with cut-off values of 5 to 7. ASDAS (or alternatively BASDAI) may be used in cases with axial involvement. There was also consensus to include the Psoriatic arthritis Impact of Disease questionnaire (PsAID) for the assessment of patients' quality of life in follow-up consultations. The proposed definition of clinical remission in PsA is the absence of disease activity assessed using DAPSA or MDA (and/or aSDAS in patients with axial involvement), and the absence of later radiological progression. Conclusion: On the basis of the available evidence and expert consensus, recommendations have been made for disease activity assessment in PsA and a proposal for definition of clinical remission was made that may be useful in the management of PsA patients Disclosure of interests: None declared